A sintered base material and its preparation method and sintering method
By sorting the sintered rebate and blast furnace rebate by particle size, mixing it with sintered ore powder, flux and binder, a high-strength sintered base material is prepared, which solves the problems of reduced output of sintered ore products and high production costs, and achieves an efficient and stable sintering process.
Patent Information
- Application Number
- CN202211606006.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-12-14
AI Technical Summary
The use of existing sintering base materials has led to a decrease in the output of sintered ore finished products, an increase in fuel and energy consumption, an increase in equipment loss and production costs, and the existing alternatives have problems such as poor spherical properties, low strength, and inconsistent chemical composition.
By sorting the sintered rebate and blast furnace rebate by particle size, mixing with sintered ore powder, flux and binder in a specific proportion, mixing, pre-granulating and briquetting to prepare a sintered base material with high strength and low crushing rate.
The quantity and quality of finished products of sintered ore are improved, energy consumption and production costs are reduced, and the breathability of the sintering process and the stability of the finished product are ensured.
Smart Images

Figure CN115852141B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sintering process base material and a preparation method thereof, as well as a sintering method using the base material, and in particular to a high-strength, low-breakage-rate sintering base material and a sintering method, belonging to the technical field of metallurgy. Background Art
[0002] The production process of sintered ore generally includes batching, water mixing and granulation, material distribution, ventilation ignition and sintering, crushing, cooling, screening and granulation. The sintering process produces sintered ore and internal return ore, and the sintered finished ore is screened before entering the blast furnace to produce blast furnace return ore and return to the sintering process together with the internal return ore, and is used again in the sintering process. In sintering production, material distribution is one of the important factors affecting the output and quality indicators of sintered ore, among which the bottom material is an important link in the material distribution. In order to protect the grates of the sintering trolley and improve the air permeability of the sintering material layer, a layer of 20mm~40mm bottom material needs to be laid on the trolley before the sintering mixture is distributed. The bottom material is a part of the finished sintered ore with a particle size of 10mm~20mm, which becomes sintered ore again after sintering. Generally, the amount of bottom material used accounts for about 10~14% of the sintered finished ore. The use of sintered finished ore as bottom material causes a significant decrease in the output of sintered ore finished products. The bottom material, together with the return ore from the sintering furnace and the return ore from the blast furnace that re-enters the sintering ingredients, is recycled and sintered repeatedly during the sintering production process, which not only leads to a low output rate of sintered finished ore, but also causes additional consumption of fuel, electricity and other energy and equipment loss, increasing the cost of sintered ore production.
[0003] At present, some patents and documents have proposed technical solutions for the replacement of sintering bottom materials. The Chinese patent with the authorization number CN104762468B discloses a sintering method for sintering bottom materials, which mixes sintering dust, gas ash, converter dust, bentonite and other materials in a certain ratio to make 7-20mm bottom material balls to replace the sintered ore bottom materials, so as to save the finished sintered ore and utilize various types of dust. The Chinese patent with the authorization number CN 110592371B discloses a sintering process for using large-particle sintered powder ore as sintering bottom materials. Before the sintering machine is filled with the mixed material, a 30mm thick super-special powder ore with a particle size of ≥10mm is laid in the sintering machine to replace the conventional bottom materials, thereby improving the sintered ore product quantity and the quality indicators of the finished mineral products. Authorization number CN103031430B discloses a method for manufacturing sintering base material using high-proportion return ore, wherein 50% to 75% of sintering return ore, 10% to 35% of high-grade fine iron-containing miscellaneous materials, 5% to 20% of iron-containing sludge and 5% to 10% of binder are mixed and pressed into blocks, and then dried and high-temperature roasted to form agglomerates as sintering base material to improve sintering productivity and reduce production costs. In addition, in public literature reports, similar schemes also use limonite ore blocks with a certain particle size to replace sintered finished ore as sintering base material.
[0004] Regarding the replacement of sintering bed materials, various dusts are used in the prior art to make balls instead of sintered ore bed materials. There are problems such as poor balling properties of various dusts and low raw ball strength. Dust and mud raw balls are easy to break and scatter under the pressure of the sintering material layer, affecting the air permeability of the sintering material layer and generating a large amount of dust and harmful elements such as Pb and Zn into the sintering exhaust system. Large-particle sintering powder ore or limonite block ore of a certain particle size is used as sintering bed material. Since its chemical composition is different from that of sintered ore and it is mixed with sintered ore after firing, it is not conducive to the subsequent slag alkalinity adjustment of blast furnace ironmaking. The existing technical solution of using returned ore and sludge and other materials to mix and press them into a ball, and then dry and roast them as sintering bed materials, on the one hand, in order to meet the requirements of sintering for the composition and strength of raw materials and bed materials, high-temperature roasting is required, which has high energy consumption. On the other hand, some sintering harmful elements are brought in by solid waste such as sludge and iron-containing miscellaneous materials. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention proposes a sintering bed material and its preparation and application. After the sintering return ore and / or blast furnace return ore are graded according to particle size, they are matched with sintering ore powder, flux and binder with good bonding performance, and are mixed and pre-granulated and pressed to form a mass. Without the need for high-temperature roasting and without affecting the subsequent blast furnace ironmaking operation, a substitute for sintering ore bed material with satisfactory composition and strength is obtained, solving the problem that the sintering bed material reduces the amount of sintered ore finished products and the energy waste caused by the repeated sintering of return ore and bed material. The sintering bed material prepared by the present invention has high compressive strength and low breakage rate, and its composition is the same as the raw materials of the sintering process. The sintered ore obtained by sintering is of stable quality and has high conversion strength of the sintered ore.
[0006] According to a first embodiment of the present invention, a sintered primer is provided.
[0007] A sintered paving material, which is obtained by mixing and briquetting the following components: return ore I, return ore II, sintered ore powder, flux, binder, and water. The particle size of return ore I is 1-3 mm. The particle size of return ore II is greater than 3 mm. The particle size of sintered ore powder is less than 0.14 mm. The weight ratio of return ore I, return ore II, and sintered ore powder is 1-5:1-100:0.5-10.
[0008] In the present invention, the return ore I and the return ore II are both sintering return ore and / or blast furnace return ore.
[0009] In the present invention, the sintered ore powder is obtained by grinding sintered ore powder.
[0010] Preferably, the TFe content of the powder ore is greater than or equal to 55%.
[0011] In the present invention, the flux is a calcium flux.
[0012] Limestone, quicklime or slaked lime is preferred.
[0013] Preferably, the particle size of the flux is less than 0.14 mm.
[0014] In the present invention, the binder is bentonite and / or humic acid.
[0015] Preferably, the sintered ore powder has a particle size of less than 0.14 mm, and the content of particles less than 0.074 mm is greater than 60%.
[0016] Preferably, the sintered ore powder is one or more of PB powder, Newman powder, MAC powder, Yangdi powder and FMG powder.
[0017] In the present invention, the particle size of the sintered base material is 10-40 mm, preferably 12-30 mm.
[0018] Preferably, the sintered paving material is obtained by mixing, granulating and briquetting the following components:
[0019] Return ore I 0.5-40%, preferably 1-20%, more preferably 1.5-15%, more preferably 2-10%,
[0020] Return ore II 30-75%, preferably 35-70%, more preferably 40-65%, more preferably 45-60%;
[0021] Sintered ore powder 10-45%, preferably 15-40%, more preferably 18-35%, more preferably 20-30%;
[0022] Flux 2-15%, preferably 2.5-12%, more preferably 3-10%, more preferably 3.5-8%;
[0023] Binder 0.1-3%, preferably 0.2-2.8%, more preferably 0.3-2.5%, more preferably 0.4-2%;
[0024] Water: 3-15%, preferably 4-14%, more preferably 5-13%, and even more preferably 6-12%.
[0025] According to a second embodiment provided by the present invention, a method for preparing a sintered base material is provided.
[0026] A method for preparing the sintered primer described in the first embodiment, the method comprising the following steps:
[0027] (A1) screening the sintering return ore and / or the blast furnace return ore to obtain return ore I with a particle size of 1-3 mm and return ore II with a particle size greater than 3 mm;
[0028] (A2) grinding the sintering powder ore to obtain a sintered ore powder having a particle size of less than 0.14 mm;
[0029] (A3) mixing and pre-granulating the return ore I and return ore II obtained in step (1), the sintered ore powder obtained in step (2), a flux, a binder, and water according to a weight ratio to obtain a granulated material;
[0030] (A4) The granulated material is pressed into a pelletizing device to form a shaped agglomerate, and the shaped agglomerate is used as a sintering base material.
[0031] Preferably, in step (A1), the sintering return ore and / or the blast furnace return ore are screened, and the return ore with a particle size of less than 1 mm is used as a sintering raw material.
[0032] Preferably, in step (A4), the formed agglomerates are sieved and those with a particle size of 10-40 mm (preferably 12-30 mm) are used as sintering base materials.
[0033] Preferably, the formed agglomerates that do not meet the particle size requirements are returned to step (A3).
[0034] According to a third embodiment of the present invention, a sintering method is provided.
[0035] A sintering method, the method comprising the following steps:
[0036] (B1) Laying the sintering base material described in the first embodiment or the sintering base material prepared according to the method described in the second embodiment on a trolley of a sintering machine;
[0037] (B2) laying sintering raw materials on the sintering base material;
[0038] (B3) Ignite and sinter the materials in the sintering machine car to obtain sintered ore.
[0039] Preferably, the sintered ore is screened to obtain sintered return ore, and then the sintered return ore is screened according to the particle size to obtain return ore I and return ore II.
[0040] In the present invention, the laying thickness of the sintering base material is 20-50 mm. The total thickness of the sintering base material and the sintering raw material is 500-1000 mm.
[0041] Preferably, the particle size of the sintered primer and the laying thickness of the sintered primer are determined according to the total thickness of the sintered primer and the sintered raw material, which is specifically:
[0042] When the total thickness of the sintering base material and the sintering raw material is 500-600mm, the particle size of the sintering base material is controlled to be 10-15mm, and the laying thickness of the sintering base material is 20-30mm;
[0043] When the total thickness of the sintering base material and the sintering raw material is 600-800mm, the particle size of the sintering base material is controlled to be 15-25mm, and the laying thickness of the sintering base material is 30-40mm;
[0044] When the total thickness of the sintering base material and the sintering raw material is 800-1000mm, the particle size of the sintering base material is controlled to be 25-40mm, and the laying thickness of the sintering base material is 40-50mm.
[0045] In the sintering process of the prior art, the sintered finished ore obtained after the sintering process is screened, and the sintered ore with a particle size of less than 5 mm is returned to the sintering raw material batching process, re-mixed into the sintering raw materials, and sintered again after mixed granulation; the sintered ore with a particle size of less than 5 mm accounts for about 10% of the entire sintered ore. The sintered ore with a particle size greater than 20 mm is used as a base material for the sintering process, and this part of the sintered ore accounts for about 10% of the entire sintered ore. The sintered ore with a particle size between 5-20 mm enters the blast furnace process. In other words, the utilization rate of the sintered ore obtained by the sintering process in the prior art is about 80%.
[0046] In the prior art, there is a technical solution for mixing fine-grained materials such as sintering dust, gas ash, and dust mud with a binder for granulation to obtain sintering base material. Since all fine-grained materials are used, the ball-forming performance is poor. The sintering base material obtained by this technology has a low compressive strength and a high breakage rate after sintering, which affects the air permeability of the sintering material layer and generates a large amount of dust. In the prior art, super-special powder is mixed with returned ore, and fuel, binder, flux and other materials are added for granulation to obtain sintering base material. Experiments have found that due to the large proportion of super-special powder and the large particle size of super-special powder, the obtained sintering base material has poor ball-forming performance and is easy to burst during the sintering process; and the super-special powder itself needs to be sintered. The large-particle super-special powder is used as a base material, and the sintering effect in the sintering process is poor, and the quality of the sintered ore obtained is low. The existing technology mixes return ore, high-grade fine-grained iron-containing miscellaneous materials, sludge, binder and other materials to obtain sintering bed material. Experiments have found that the particle size of the return ore is uneven and the return ore content of each particle size is unstable, resulting in unstable compressive strength of the prepared sintering bed material. The sintering bed material in the entire sintering machine trolley is uneven, causing the bed material to break, affecting the air permeability of the sintering process, and further affecting the quality of the sintered ore. In addition, the process requires a roasting process in advance, which greatly affects the efficiency of the sintering process.
[0047] The present invention adopts the technology of classifying the particle size of the return ore to obtain return ore with different particle sizes of less than 1mm, 1-3mm, and greater than 3mm. By reasonably adjusting the proportion of the return ore with different particle sizes used as the base material, adding a suitable proportion of sintered ore powder, flux and binder, the sintered base material is directly obtained through mixing, granulation and briquetting processes. The compressive strength of the prepared sintered base material is greatly improved. The sintered base material is prepared according to the appropriate proportion of the return ore with different particle sizes, and the ball forming performance is good and the green ball strength is high; the sintered base material is used for sintering, and the breakage rate of the base material is greatly reduced, reducing the dust generation of the sintering process. In addition, the sintered ore powder with small particle size is used, the material components are similar, and the ball forming performance is good, thereby ensuring the quality of the sintered ore obtained through the sintering process. The present invention controls the proportion of various materials by using return ore of different particle sizes and sintered ore powder of small particle size to obtain a high-strength sintered ore base material; the return ore has undergone a sintering process, and the large particle size does not affect the quality of the sintered ore. The sintered ore powder of small particle size is all iron-containing material, which is easy to achieve the sintering effect in the sintering process, ensuring the quality of the entire sintered ore. The sintered ore base material obtained by mixing materials of large and small particle sizes in a controlled ratio has good balling performance and high strength, ensuring the air permeability of the sintering process, and thus ensuring the quality of the sintered ore.
[0048] The inventors have found through experiments that controlling the addition ratio of different particle size return ore in the raw materials for preparing sintering bed material can improve the balling performance of the sintering bed material, and also greatly improve the compressive strength of the sintering bed material. The particle size and compressive strength of the bed material are guaranteed, thereby ensuring the integrity of the bed material in the sintering process and the air permeability of the sintering process. If the bed material is damaged, the damaged material will be compacted on the trolley, causing the gas to be blocked from passing through the sintering machine trolley during the sintering process, which affects the air permeability of the entire sintering process, thereby affecting the quality of the sintered ore.
[0049] In the present invention, the return ore I and return ore II are both sintered return ore and / or blast furnace return ore. The sintered return ore is a sintered ore with a particle size of less than 5 mm produced after sintering, cooling and screening of the sintered raw materials. The blast furnace return ore refers to a sintered ore with a particle size of less than 5 mm produced by screening before entering the blast furnace. It is mainly produced because the sintered ore with a particle size greater than 5 mm is broken and crushed during transportation and transfer.
[0050] In the present invention, the sintered ore powder is obtained by grinding the powder ore for sintering. The ore powder of the raw material for sintering is ground to obtain the sintered ore powder with a particle size less than 0.14 mm. Preferably, the TFe content in the powder ore for sintering is greater than or equal to 55%. Preferably, the sintered ore powder has a particle size less than 0.14 mm and a content of particles less than 0.074 mm greater than 60%.
[0051] In the present invention, the return ore with a particle size of 1-3 mm, the return ore with a particle size greater than 3 mm, and the sintered ore powder with a particle size less than 0.14 mm are mixed in proportion, and a flux, a binder and water are added. After uniform mixing, granulation and briquetting, a high-strength sintered base material is directly obtained. The obtained base material is directly laid on the sintering machine trolley (without sintering and other processes) and used as the base material.
[0052] In the present invention, the sintering base material obtained by mixing specific components and specific proportions is controlled to have a particle size of 10-40 mm, preferably 12-30 mm, according to the thickness of the material on the sintering machine trolley.
[0053] The inventor found through experiments that the return ore used to prepare the sintering bed material cannot use the return ore with a particle size less than 1mm (the material with a particle size less than 1mm in the return ore accounts for about 13-17% of the whole return ore). Since the return ore is a sintered material, the bonding performance is extremely poor, and the return ore with a particle size too small cannot be balled. Some small-sized return ore can only adhere to the surface of the bed material. The small-sized return ore adhered to the surface is very easy to separate from the bed material in the sintering process and enter the sintering flue gas, which can not play the role of the bed material at all, and increases the dust content in the sintering flue gas. It is better to control the weight ratio of the return ore with a particle size of 1-3mm and the return ore with a particle size greater than 3mm in the return ore used to prepare the sintering bed material in the range of 1-5:1-100. It was found through experiments that based on the weight of the entire sintered base material, the added amount of return ore I was controlled at 2-10% (for example 3%, 4%, 5%, 6%, 7%, 8%, 9%), the added amount of return ore II was controlled at 45-60% (for example 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%), and the added amount of sintered ore powder was controlled at 20-30% (for example 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%). The green ball compressive strength of the obtained sintered base material reached more than 1000N, and the breakage rate of the base material was less than 1% when the sintered base material was used for sintering.
[0054] According to the experiment, the addition amount of return ore I is controlled at 0.5-40%, the addition amount of return ore II is controlled at 30-75%, and the addition amount of sintered ore powder is controlled at 10-45%. The green ball compressive strength of the obtained sintered bed material reaches more than 800N. When the sintered bed material is used for sintering, the crushing rate of the bed material is less than 5%. The addition amount of return ore I is controlled at 1-20%, the addition amount of return ore II is controlled at 35-70%, and the addition amount of sintered ore powder is controlled at 15-40%. The green ball compressive strength of the obtained sintered bed material reaches more than 850N. When the sintered bed material is used for sintering, the crushing rate of the bed material is less than 4%. The added amount of return ore I is controlled at 1.5-15%, the added amount of return ore II is controlled at 40-65%, and the added amount of sintered ore powder is controlled at 18-35%. The green ball compressive strength of the obtained sintered base material reaches more than 900N. When the sintered base material is used for sintering, the crushing rate of the base material is less than 3%.
[0055] Through experiments, it is found that the green ball compressive strength of sintered bedding material and the breakage rate of bedding material after sintering are directly related to the composition of sintered bedding material. By reasonably controlling the composition of sintered bedding material (controlling the particle size) and the amount of each component added, the green ball compressive strength of sintered bedding material can be improved and the breakage of sintered bedding material during sintering process can be reduced.
[0056] In the present invention, the technical solution provided by the present invention is adopted to carry out the sintering process, and the obtained sintered ore is screened, and the ore with a particle size less than 5 mm is the sintering return ore (accounting for about 10% of the whole sintered ore), and the sintered ore with a particle size greater than 5 mm directly enters the blast furnace process. By adopting the process of the present invention, the utilization rate of the sintered ore reaches more than 90%. The sintered ore with a particle size less than 5 mm is screened, and all the particles with a particle size of 3-5 mm are used to prepare the sintering base material. The sintered ore with a particle size of 1-3 mm is used to prepare the sintering base material according to the weight ratio, and the remaining part is added to the sintering raw material. All the particles with a particle size less than 1 mm are added to the sintering raw material.
[0057] Through experimental verification, it is found that according to the thickness of the material to be laid on the sintering machine trolley, controlling the particle size of the sintering base material and the thickness of the sintering base material can effectively improve the air permeability of the sintering process and reduce the damage of the sintering base material. Specifically, when the total thickness of the sintering base material and the sintering raw material is 500-600mm, the particle size of the sintering base material is controlled to be 10-15mm, and the laying thickness of the sintering base material is 20-30mm; when the total thickness of the sintering base material and the sintering raw material is 600-800mm, the particle size of the sintering base material is controlled to be 15-25mm, and the laying thickness of the sintering base material is 30-40mm; when the total thickness of the sintering base material and the sintering raw material is 800-1000mm, the particle size of the sintering base material is controlled to be 25-40mm, and the laying thickness of the sintering base material is 40-50mm.
[0058] The present invention provides a sintering bed material, which is formed by mixing and pressing materials such as sintered return ore after particle size classification in different proportions, finely ground sintered ore powder with good ball-forming and agglomeration performance, flux and binder, etc. The strength can be adjusted according to the height of the sintering material layer, and the basicity is kept consistent with the sintered ore. It can replace conventional sintering bed materials to increase the output of sintered finished ore, reduce the amount of sintering return ore directly returned to the sintering process, and reduce the energy waste caused by repeated sintering of sintered ore bed materials and return ore.
[0059] The present invention also provides a method for preparing and using a sintered base material, the process flow is as follows: Figure 1 The present invention provides a method for preparing and using a sintered base material, and the detailed steps are as follows:
[0060] (1) The sintered return ore is screened to obtain return ore of different particle sizes, namely, <1 mm, 1 mm to 3 mm, and >3 mm, wherein the return ore of particle size <1 mm and part of the return ore of 1 mm to 3 mm (sintered return ore I) are returned to the sintering batching, and the return ore of particle size >3 mm (sintered return ore II) and part of the sintered return ore I are used as raw materials for preparing sintering base material.
[0061] The returned ore is screened and graded for utilization. The technical principle and beneficial effects are as follows: First, the coarser particles and some of the intermediate particles are used to prepare the base material. During the molding process, the returned ore particles can play a role of skeleton support, promote the molding of agglomerates, and improve the strength of the molded agglomerates; Second, within the appropriate particle size range, the larger the particle size of the returned ore particles, the stronger the skeleton support they play for the molded agglomerates and the higher the strength of the agglomerates. When the sintering cloth has different requirements for the strength of the base material, the ratio of the returned ore with a particle size of >3mm and 1-3mm can be adjusted to make the molded agglomerates meet the requirements, thereby reducing the binder ratio and cost; Third, the returned ore with a particle size of <1mm and some of the 1-3mm particle size is returned for sintering, which maintains the positive role of the returned ore particles as the granulation core and the returned ore in promoting the formation of melt during the sintering process.
[0062] (2) Sintered ore return I, sintered ore return II, finely ground sintered ore powder, flux, binder, water and other materials are weighed and measured according to specific proportions, and then all materials are mixed and pre-granulated. Among them, the sintered ore powder is obtained by grinding the sintering powder ore, and the types of powder ore include mainstream varieties in the iron ore market such as Newman powder, MAC powder, Yangdi powder, FMG, etc., with a TFe content of 55%-62%, and the finely ground sintered powder ore has a particle size of <0.14mm and a particle content of <0.074mm>60%; the calcium flux is limestone, quicklime or lime milk, and the particle size is <0.14mm; the binder is an inorganic or organic binder such as bentonite and humic acid; the mixing and pre-granulation equipment uses a cylindrical mixing granulator or a strong mixing granulator.
[0063] Sintered ore powder and flux are used as raw materials, and the technical principles and beneficial effects are as follows: First, the good natural bonding properties of sintered ore powder are utilized, combined with the skeleton support effect of coarse return ore particles, supplemented with a small amount of binder, so that the formed agglomerates can have higher strength; second, after the sintered powder ore is finely ground, the surface activity of the particles is higher, and the agglomerates have a fast consolidation speed and high strength during the short-term high-temperature process at the end of sintering; third, the addition of calcium flux, on the one hand, makes the basicity of the formed agglomerates consistent with the sintered ore to avoid affecting the adjustment of the basicity of blast furnace slag making, and on the other hand, promotes the high-temperature consolidation of the agglomerates and improves their strength.
[0064] (3) The mixed and pre-granulated materials are pressed into balls in a ball pressing device. The finished agglomerates obtained after the discharge is screened are the sintering base materials. The screened materials are returned and pressed into balls again together with the mixed materials.
[0065] Among them, the groove diameter of the ball pressing molding equipment is 17mm~35mm, the discharge screening aperture is 15mm; the particle size of the formed agglomerates is 10mm~40mm, and the compressive strength is 800~1500N; the particle size of the undersize material is 0~10mm, and after returning, it is formed and pressed together with the mixed material to increase the feed volume density, improve the material forming rate and strength.
[0066] (4) The formed agglomerates are used as sintering base materials and transported to the sintering machine head via a belt for distribution, with a distribution thickness of 20mm-50mm. Then the sintering mixture obtained after conventional sintering ingredients, mixing and granulation is distributed, with a distribution height of 500mm-1000mm. Subsequently, ignition sintering is carried out, and the sintered cakes are crushed, cooled, and screened to obtain the finished sintered ore.
[0067] The forming agglomerates prepared by the invention are used to replace the conventional sintering ore bed material. The technical principle and beneficial effects are as follows: first, compared with the conventional sintering ore bed material (the particle size is generally 10mm-20mm and the shape is irregular), the forming agglomerates prepared by the present invention have larger particle size and regular shape, and the permeability of the bed material layer and the sintering material layer is higher, which can increase the height of the sintering material layer and improve the quality index of the sintered ore; second, according to the change of the height of the sintering material layer, the size of the forming agglomerates, the thickness of the cloth and the ratio of the different particle size return ore during the preparation of the agglomerates are adjusted in time to achieve the matching of the agglomerate strength, size and thickness to the height of the sintering material layer; third, the forming agglomerates are gradually heated and dried during the sintering process, and then the consolidation and liquid phase encapsulation reactions occur at a short time high temperature when the sintering reaches the end point, directly forming sintered ore products, and increasing the output of sintered ore. In addition, after using the bed material proposed by the present invention, the screens other than the 5mm screen in the sintering ore screening chamber can be completely or partially cancelled, reducing equipment investment and screening energy consumption.
[0068] Compared with the prior art, the technical solution provided by the present invention has the following beneficial technical effects:
[0069] 1. The present invention provides a sintering bed material, which is a shaped agglomerate obtained by mixing and pressing the returned ore after particle size classification with finely ground sintered ore powder, flux, binder and other materials in different proportions. The shape is regular, the strength is high, and the basicity is consistent with the sintered ore. It can not only maintain the positive effect of the returned ore particles on the granulation and sintering process, but also meet the requirements of the sintering material layer height on the bed material strength. Replacing the conventional sintered ore bed material can increase the output of sintered finished ore and reduce the waste of sintering energy.
[0070] 2. The present invention provides a sintering base material and a preparation method thereof. The return ore after particle size classification is mixed with finely ground sintered ore powder, flux, binder, etc. in different proportions for pre-granulation and then pressed into blocks. The good natural bonding performance of the finely ground sintered powder ore and the skeleton support role of the return ore particles in the pressing and molding process are combined. The amount of binder used is small and the strength of the molded agglomerates is high. It can be directly used as a sintering base material without the need for separate drying and roasting treatments. The finely ground sintered powder particles have higher activity, and the agglomerates are easier to consolidate under high temperature for a short time at the end of sintering.
[0071] 3. The present invention provides a sintering base material and a preparation and use method thereof. The prepared formed agglomerates are used to replace conventional sintering ore base materials, which can significantly improve the air permeability of the sintering material layer. At the same time, the material thickness, specification size and ratio of different particle size return ore during agglomerate preparation of the formed agglomerates can be adjusted according to changes in the sintering height, taking into account the sintering granulation effect and the air permeability of the sintering material layer, thereby improving the quality indicators of the sintered ore. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 A process flow chart for preparing a sintering base material for sintering by using the technical solution provided by the present invention;
[0073] Figure 2 This is a physical picture of the sintered base material product prepared by the technical solution provided by the present invention;
[0074] Figure 3 A physical picture of a product that uses the technical solution provided by the present invention to prepare a sintered base material for use as a base material after sintering. DETAILED DESCRIPTION
[0075] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.
[0076] According to a first embodiment of the present invention, a sintered primer is provided.
[0077] A sintered paving material, which is obtained by mixing and briquetting the following components: return ore I, return ore II, sintered ore powder, flux, binder, and water. The particle size of return ore I is 1-3 mm. The particle size of return ore II is greater than 3 mm. The particle size of sintered ore powder is less than 0.14 mm. The weight ratio of return ore I, return ore II, and sintered ore powder is 1-5:1-100:0.5-10.
[0078] In the present invention, the return ore I and the return ore II are both sintering return ore and / or blast furnace return ore.
[0079] In the present invention, the sintered ore powder is obtained by grinding sintered ore powder.
[0080] Preferably, the TFe content of the powder ore is greater than or equal to 55%.
[0081] In the present invention, the flux is a calcium flux.
[0082] Limestone, quicklime or slaked lime is preferred.
[0083] Preferably, the particle size of the flux is less than 0.14 mm.
[0084] In the present invention, the binder is bentonite and / or humic acid.
[0085] Preferably, the sintered ore powder has a particle size of less than 0.14 mm, and the content of particles less than 0.074 mm is greater than 60%.
[0086] Preferably, the sintered ore powder is one or more of PB powder, Newman powder, MAC powder, Yangdi powder and FMG powder.
[0087] In the present invention, the particle size of the sintered base material is 10-40 mm, preferably 12-30 mm.
[0088] Preferably, the sintered paving material is obtained by mixing, granulating and briquetting the following components:
[0089] Return ore I 0.5-40%, preferably 1-20%, more preferably 1.5-15%, more preferably 2-10%,
[0090] Return ore II 30-75%, preferably 35-70%, more preferably 40-65%, more preferably 45-60%;
[0091] Sintered ore powder 10-45%, preferably 15-40%, more preferably 18-35%, more preferably 20-30%;
[0092] Flux 2-15%, preferably 2.5-12%, more preferably 3-10%, more preferably 3.5-8%;
[0093] Binder 0.1-3%, preferably 0.2-2.8%, more preferably 0.3-2.5%, more preferably 0.4-2%;
[0094] Water: 3-15%, preferably 4-14%, more preferably 5-13%, and even more preferably 6-12%.
[0095] In the embodiments of the present invention, the particle sizes of the PB powder, Newman powder, MAC powder, Yangdi powder and FMG powder used are all less than 0.14 mm, and the iron grade and TFe content thereof are all greater than 55%.
[0096] Example 1
[0097] The materials were weighed according to the proportions of 33 parts by weight of 1-3mm sintered return ore, 33 parts by weight of >3mm sintered return ore, 20 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 1.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment with a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16mm and a maximum thickness of 12mm.
[0098] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0099] Example 2
[0100] The materials were weighed according to the proportions of 16 parts by weight of sintered ore with a diameter of 1-3 mm, 50 parts by weight of sintered ore with a diameter of >3 mm, 20 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 1.5 parts by weight of humic acid and 8 parts by weight of water. After pretreatment with a vertical high-power mixing granulator, the materials were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0101] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 800 mm, and then ignited and sintered.
[0102] Example 3
[0103] The materials were weighed according to the proportions of 10 parts by weight of sintered ore with a diameter of 1-3 mm, 50 parts by weight of sintered ore with a diameter of >3 mm, 26 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 1.5 parts by weight of humic acid and 8 parts by weight of water. After pretreatment with a vertical high-power mixing granulator, the materials were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 20 mm and a maximum thickness of 15 mm.
[0104] The finished lumps are used as sintering base material with a thickness of 40mm-50mm and a sintering base material height of 950mm, and then ignited and sintered.
[0105] Example 4
[0106] The materials were weighed according to the proportions of 8 parts by weight of 1-3mm sintered return ore, 53 parts by weight of >3mm sintered return ore, 25 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 1.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0107] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0108] Example 5
[0109] The materials were weighed according to the proportions of 5 parts by weight of 1-3mm sintered return ore, 56 parts by weight of >3mm sintered return ore, 25 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 1.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16mm and a maximum thickness of 12mm.
[0110] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0111] Example 6
[0112] The materials were weighed according to the proportions of 3 parts by weight of 1-3mm sintered return ore, 58 parts by weight of >3mm sintered return ore, 25 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 1.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16mm and a maximum thickness of 12mm.
[0113] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0114] Example 7
[0115] The materials were weighed according to the proportions of 15 parts by weight of 1-3 mm sintered return ore, 51 parts by weight of >3 mm sintered return ore, 15 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 1.5 parts by weight of humic acid, and 8 parts by weight of water. After pre-treatment with a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0116] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0117] Example 8
[0118] The materials were weighed according to the proportions of 20 parts by weight of 1-3mm sintered return ore, 56 parts by weight of >3mm sintered return ore, 10 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 1.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment with a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0119] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0120] Example 9
[0121] Example 3 was repeated except that quicklime was used instead of limestone.
[0122] Example 10
[0123] Example 3 was repeated except that slaked lime was used instead of limestone.
[0124] Embodiment 11
[0125] Example 3 was repeated except that bentonite was used instead of humic acid.
[0126] Example 12
[0127] Example 3 was repeated except that PB powder was used instead of Newman powder.
[0128] Example 13
[0129] Example 3 was repeated except that MAC powder was used instead of Newman powder.
[0130] Embodiment 14
[0131] Example 3 was repeated except that Yangdi powder was used instead of Newman powder.
[0132] Embodiment 15
[0133] Example 3 was repeated except that FMG powder was used instead of Newman powder.
[0134] Comparative Example 1
[0135] The sintered ore was not screened. The materials were weighed according to the ratio of 70 parts by weight of sintered ore, 12 parts by weight of ordinary iron concentrate, 6 parts by weight of iron-containing sludge, 3 parts by weight of bentonite, 4 parts by weight of starch and 5 parts by weight of water. After pretreatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0136] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0137] Comparative Example 2
[0138] The conventional sintered ore is screened, and the sintered ore with a particle size greater than 20 mm is used as the base material. The base material thickness is 25 mm, and the sintering material height is 700 mm. Then ignition and sintering are carried out.
[0139] Comparative Example 3
[0140] The materials were weighed according to the proportions of 6 parts by weight of 1-3mm sintered return ore, 30 parts by weight of >3mm sintered return ore, 50 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 2.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16mm and a maximum thickness of 12mm.
[0141] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0142] Comparative Example 4
[0143] The materials were weighed according to the ratio of 80 parts by weight of sintered return ore with diameter >3 mm, 12 parts by weight of finely ground Newman powder, 2.5 parts by weight of limestone, 0.5 parts by weight of humic acid and 5 parts by weight of water. After pre-treatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0144] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0145] Comparative Example 5
[0146] The materials were weighed according to the ratio of 12 parts by weight of sintered ore with a diameter of 1-3 mm, 80 parts by weight of sintered ore with a diameter greater than 3 mm, 2.5 parts by weight of limestone, 0.5 parts by weight of humic acid and 5 parts by weight of water. After pre-treatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0147] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0148] Comparative Example 6
[0149] The materials were weighed according to the proportions of 46 parts by weight of 1-3 mm sintered return ore, 20 parts by weight of >3 mm sintered return ore, 20 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 2.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0150] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0151] Comparative Example 7
[0152] The materials were weighed according to the proportions of 50 parts by weight of 1-3 mm sintered return ore, 16 parts by weight of >3 mm sintered return ore, 20 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 2.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment with a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0153] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0154] Comparative Example 8
[0155] The materials were weighed according to the ratio of 86 parts by weight of 1-3 mm sintered return ore, 4.5 parts by weight of limestone, 2.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0156] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0157] Comparative Example 9
[0158] The materials were weighed according to the ratio of 86 parts by weight of sintered return ore with diameter greater than 3 mm, 4.5 parts by weight of limestone, 2.5 parts by weight of humic acid and 8 parts by weight of water. After pre-treatment by a vertical high-power mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0159] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0160] Comparative Example 10
[0161] The materials were weighed according to the ratio of 86 parts by weight of finely ground Newman powder, 4.5 parts by weight of limestone, 2.5 parts by weight of humic acid and 8 parts by weight of water, and after pretreatment by a vertical high-intensity mixing granulator, they were pressed into agglomerates using a ball press to obtain finished agglomerates with a diameter of 16 mm and a maximum thickness of 12 mm.
[0162] The finished agglomerates are used as sintering base material with a thickness of 25 mm and a sintering base material height of 700 mm, and then ignited and sintered.
[0163] According to the technical solutions provided in the above embodiments and comparative examples, the compressive strength of the finished lumps used as sintering base materials was tested, the damage of the sintering base materials after the sintering process was tested (weighing and calculating the ratio), the sintering utilization coefficient of each technical solution was calculated, and the drum strength of the entire sintered ore after the sintering process was tested; the results are shown in the following table.
[0164]
[0165]
[0166] In the present invention, the compression strength of the agglomerates is tested in accordance with the standard "Method for Determination of Compression Strength of Iron Ore Pellets" GB / T14201. The sintering utilization coefficient is calculated in accordance with the standard "Design Specifications for Sintering Plants" GB50408. The drum strength is tested in accordance with the standard "Method for Determination of Drum Strength of Sintered Ore and Pellets" GB / T 8209.
[0167] The breakage rate of the sintered bedding material after the sintering process = the weight of the sintered bedding material that remains intact after sintering / (the weight of the sintered bedding material finished agglomerate - the weight of water)*100%.
Claims
1. A sintered base material, characterized in that: The sintered paving material is obtained by mixing, granulating and briquetting the following components; Return ore I 0.5-40%, return ore II 30-75%, sintered ore powder 10-45%, flux 2-15%, binder 0.1-3%, water 3-15%; wherein: the particle size of return ore I is 1-3mm, the particle size of return ore II is greater than 3mm, and the particle size of sintered ore powder is less than 0.14mm; the sintered ore powder is obtained by grinding sintering powder ore; the return ore I and return ore II are both sintered return ore and / or blast furnace return ore.
2. The sintered base material according to claim 1, characterized in that: Return ore I 1-20%, return ore II 35-70%, sintered ore powder 15-40%, flux 2.5-12%, binder 0.2-2.8%, water 4-14%.
3. The sintered base material according to claim 2, characterized in that: Return ore I 1.5-15%, return ore II 40-65%, sintered ore powder 18-35%, flux 3-10%, binder 0.3-2.5%, water 5-13%.
4. The sintered base material according to claim 3, characterized in that: Return ore I 2-10%, return ore II 45-60%, sintered ore powder 20-30%, flux 3.5-8%, binder 0.4-2%, water 6-12%.
5. The sintered base material according to any one of claims 1 to 4, characterized in that: The TFe content of the powder ore is greater than or equal to 55%; and / or The flux is a calcium flux; and / or The binder is bentonite and / or humic acid.
6. The sintered base material according to claim 5, characterized in that: The flux is limestone, quicklime or slaked lime.
7. The sintered base material according to any one of claims 1 to 4 and 6, characterized in that: The particle size of the flux is less than 0.14 mm.
8. The sintered base material according to any one of claims 1 to 4 and 6, characterized in that: The sintered ore powder has a particle size of less than 0.14 mm, and the content of particles less than 0.074 mm is greater than 60%.
9. The sintered base material according to any one of claims 1 to 4 and 6, characterized in that: The sintered ore powder is one or more of PB powder, Newman powder, MAC powder, Yangdi powder and FMG powder.
10. The sintered base material according to any one of claims 1 to 4 and 6, characterized in that: The particle size of the sintered base material is 10-40 mm.
11. The sintered base material according to claim 10, characterized in that: The particle size of the sintered base material is 12-30 mm.
12. A method for preparing the sintered base material according to any one of claims 1 to 11, the method comprising the following steps: A1) sieving the sintered ore and / or the blast furnace ore to obtain ore I with a particle size of 1-3 mm and ore II with a particle size greater than 3 mm; A2) grinding the sintering powder ore to obtain sintered ore powder with a particle size of less than 0.14 mm; A3) mixing and pre-granulating the return ore I and return ore II obtained in step A1), the sintered ore powder obtained in step A2), a flux, a binder, and water according to a weight ratio to obtain a granulated material; A4) The granulated material is pressed into a pelletizing device to form a shaped agglomerate, and the shaped agglomerate is used as a sintering base material.
13. The method according to claim 12, characterized in that: In step A1), the sintering return ore and / or blast furnace return ore are screened, and the return ore with a particle size of less than 1 mm is used as a sintering raw material; and / or In step A4), the formed agglomerates are screened, and those with a particle size of 10-40 mm are used as sintering base materials.
14. The method according to claim 13, characterized in that: The formed agglomerates that do not meet the particle size requirements are returned to step A3).
15. A sintering method, the method comprising the following steps: B1) laying the sintering bedding material according to any one of claims 1 to 11 or the sintering bedding material prepared by the method according to any one of claims 12 to 14 on a trolley of a sintering machine; B2) laying sintering raw materials on the sintering base material; B3) Ignite and sinter the materials in the sintering machine trolley to obtain sintered ore.
16. The sintering method according to claim 15, characterized in that: The sintered ore is screened to obtain sintered return ore, and then the sintered return ore is screened according to the particle size to obtain return ore I and return ore II.
17. The sintering method according to claim 15 or 16, characterized in that: The laying thickness of the sintering base material is 20-50mm; the total thickness of the sintering base material and the sintering raw material is 500-1000mm.
18. The sintering method according to claim 17, characterized in that: When the total thickness of the sintering base material and the sintering raw material is 500-600mm, the particle size of the sintering base material is controlled to be 10-15mm, and the laying thickness of the sintering base material is 20-30mm; When the total thickness of the sintering base material and the sintering raw material is 600-800mm, the particle size of the sintering base material is controlled to be 15-25mm, and the laying thickness of the sintering base material is 30-40mm; When the total thickness of the sintering base material and the sintering raw material is 800-1000mm, the particle size of the sintering base material is controlled to be 25-40mm, and the laying thickness of the sintering base material is 40-50mm.
Citation Information
Patent Citations
Method for making sintering bed charge by returning mine at high mixture ratio
CN103031430B
A sintering method for sintering bed material
CN104762468B
A sintering process for using large-particle ultra-fine powder as a sintering substrate
CN110592371B
Sintering mixture and mixing method, sintering ore and sintering method
CN111560516A